Effect of ACTH4-10pro8-gly9-pro10 on malondialdehyde and F2-isoprostane 15(S)-8-iso-PGF2a expression in rat spinal cord injury - Destiansyah, Rifqi Aulia; Subagio, Eko Agus; Parenrengi, Muhammad Arifin; Utomo, Budi; Faris, Muhammad; Bajamal, Abdul Hafid; Abdillah, Diaz Syafrie (Gaceta Médica de Caracas, 2023)
Background: Spinal cord injury (SCI) is damage to the spinal cord caused mainly by trauma resulting in major motor, sensory, and autonomic dysfunctions. This experimental study aims to assess the effect of ACTH4-10Pro8-Gly9-Pro10 administration in rats with mild and severe compression injuries on the levels of malondialdehyde and F2-isoprostane 15(S)-8-iso-PGF2α levels. Methods: Mild and severe spinal cord compression was performed on 27 subjects. They were divided into three groups of samples with control included, 3 and 6 h after the injury.